2014
DOI: 10.1007/s00262-014-1626-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor ablation by intratumoral Ra-224-loaded wires induces anti-tumor immunity against experimental metastatic tumors

Abstract: CT26 model: 63-77 % of DaRT-treated mice became resistant to a re-inoculated tumor compared to 29-33 % resistant mice in the control. DA3 model: (1) The growth rate of challenge tumors was the lowest in mice which their primary tumor was treated by DaRT. (2) Most (93 %) mice in the control group developed lung metastases compared to 56 % in the DaRT group. (3) Combining DaRT with CpG resulted in a better control of the primary tumor. Our study offers a technique to eliminate local and distant malignant cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 28 publications
1
27
0
2
Order By: Relevance
“…The current study represents an excellent example of successful recapitulation and validation of preclinical studies that demonstrated impressive tumor responses. [1][2][3][4][8][9][10][11][12] The innovative development of a brachytherapy dose delivery that takes advantage of short-range diffusion of alpha particles is unique and could potentially be paradigm changing. Brachytherapy has relied on radioactive beta and gamma sources for many years, and new, radio-biologically more potent sources could provide great benefit for patients with other solid tumors whose prognosis is poor.…”
Section: Months After Dart Insertionmentioning
confidence: 99%
“…The current study represents an excellent example of successful recapitulation and validation of preclinical studies that demonstrated impressive tumor responses. [1][2][3][4][8][9][10][11][12] The innovative development of a brachytherapy dose delivery that takes advantage of short-range diffusion of alpha particles is unique and could potentially be paradigm changing. Brachytherapy has relied on radioactive beta and gamma sources for many years, and new, radio-biologically more potent sources could provide great benefit for patients with other solid tumors whose prognosis is poor.…”
Section: Months After Dart Insertionmentioning
confidence: 99%
“…Their efficacy was attributed to the diffusion of the α-particle-emitting daughters of implanted 224 Ra in the tumor region surrounding the wire (114). An interesting future direction in this particular type of brachytherapy would be stimulation of specific antitumor immunity by the tumor antigens originating from the destroyed tumor (115). Studies on the effects of α-particle radiation (via radioimmunotherapy, for example), when combined with adoptive T cell transfer to induce immune responses that better control tumor growth (116), may help determine the direction of the next type of immunotherapies.…”
Section: Preclinical α-Particle Therapy Delivered By Nanometer-sizmentioning
confidence: 99%
“…Le propre de cette méthode, développée pour le traitement des tumeurs solides, est d'insérer la source radioactive (le radium-224) directement au niveau de la tumeur, ce qui libère continuellement les atomes émetteurs de particules α in situ. Les analyses effectuées à la suite de ce traitement à base de rayonnements α, pour évaluer la réponse immunitaire antitumorale, ont montré : (1) une plus grande résistance à la ré-inoculation d'une même souche tumorale (c'est-à-dire : l'inhibition de la croissance tumorale), (2) une diminution des métastases pulmonaires, et (3) un effet renforcé lorsque ces radiations sont combinées avec un immunostimulant, le CpG 4 [39,40,54] …”
Section: Le Cas Des Particules Alphaunclassified